Analisis kemampuan berpikir kreatif tema ekosistem siswa kelas V SDN Sampangan 02 Semarang - Diana Rachmawati; Rizky Esti Utami (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2023)
The research aims to describe the creative thinking skills of fifth grade students at SDN Sampangan 02 on the theme of ecosystems. This research method is a qualitative descriptive research. The subject in this study were 6 fifth grade students at SDN Sampangan 02. They consisted of 2 initial ability categories. The data collection technique in this study was a test technic in the from of student learning evaluation sheetsand interviews with students and clas teachers. The result of the study a low that: student with high-level thinking skills are able to reach the 3rt level creative catefory. They are able to fulfill indicators of fluency and flexibility. The solve the questions correclty and according to what the teacher teaches; 2) as for students with moderate initial abilities with the level 1 creative thinking level, they are only able to meet fluency indicators. They solve problems correct based on their own understanding; 3) students who have low initial ability do not show indicators of fluency, flexibility, and novelty so that they fall into the cotegory of creative thinking at level 0 (not creative). They can’t get the question right.